In Vitro Antitumor Activity of Sesquiterpene Lactones from Lychnophora trichocarpha - D.A. Saúde-Guimarães; D.S. Raslan; A.B. Oliveira (Universidade Estadual Paulista, 2014)
The sesquiterpene lactones lychnopholide and eremantholide C were isolated from Lychnophora trichocarpha Spreng. (Asteraceae), which is a plant species native to the Brazilian Savannah or Cerrado and popularly known as arnica. Sesquiterpene lactones are known to present a variety of biological activities including antitumor activity. The present paper reports on the evaluation of the in vitro antitumor activity of lychnopholide and eremantholide C, in the National Cancer Institute, USA (NCI, USA), against a panel of 52 human tumor cell lines of major human tumors derived from nine cancer types. Lychnopholide disclosed significant activity against 30 cell lines of seven cancer types with IC100 (total growth concentration inhibition) values between 0.41 µM and 2.82 µM. Eremantholide C showed significant activity against 30 cell lines of eight cancer types with IC100 values between 21.40 µM and 53.70 µM. Lychnopholide showed values of lethal concentration 50% (LC50) for 30 human tumor cell lines between 0.72 and 10.00 µM, whereas eremantholide C presented values of LC50 for 21 human tumor cell lines between 52.50 and 91.20 µM. Lychnopholide showed an interesting profile of antitumor activity. The α-methylene-γ-lactone present in the structure of lychnopholide, besides two α,β- unsaturated carbonyl groups, might be responsible for the better activity and higher cytotoxicity of this compound in relation to eremantholide C.